Qualitative Study of Anxiety among Medical Student when Facing Objective Structured Clinical Examination (OSCE) - Muhammad Mardhiya Alghifari; Hartono .; Amandha Boy Timor Randita (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Student feels that OSCE is stressfull event. Objective Structured Clinical Examination (OSCE) also induces anxiety higher than any other exam. There are fears that anxiety will impact on students because it can defend their oriented task behavior. On the other hand, excessive concerns will debilitate and annoy them in the exam if they dont manage managed it properly. This study aims to explore that anxiety problems, what are the contributing factors, and how studentss coping mechanism to deal with it. Methods: This study used a qualitative descriptive approach that wanted to describe a phenomenon occured on the subject of research. The population is an entire undergraduate Medical Student of Medical Faculty, Sebelas Maret University who have been through the OSCE. The number of samples were 32 students, that divided into four batches Focus Group Discussions and four batches interviews. This samples were taken by purposive sampling method with maximum variation sampling type. The results of FGD and interviews were analyzed by content analysis method. Results: The data found in this research were large categories of research problems included student perception about OSCE, the factors that caused OSCE anxiety, and students coping mechanism when faced with OSCE Conclusions: Anxiety happened to most of the student when they faced OSCE. Factors that triggered this anxiety were divided into internal and external factors. When faced with stressors such as OSCE, students would use two types of coping strategies, problem-focused coping and emotion-focused coping. Keywords: Anxiety, OSCE, Coping Mechanism, Medical Student